Myofascial techniques have no additional beneficial effects to a standard physical therapy programme for upper limb pain after breast cancer surgery: a randomized controlled trial. (December 2017) - De Groef, An; Van Kampen, Marijke; Vervloesem, Nele; De Geyter, Sophie; Christiaens, Marie-Rose; Neven, Patrick; Vos, Lore; De Vrieze, Tessa; Geraerts, Inge; Devoogdt, Nele
Objective: To investigate the effects of myofascial techniques, in addition to a standard physical therapy programme for upper limb pain shortly after breast cancer surgery. Design: Double-blinded (patient and assessor) randomized controlled trial with two groups. Setting: University Hospitals Leuven, Belgium Patients: A total of 147 patients with unilateral axillary clearance for breast cancer. Intervention: All participants received a standard physical therapy programme starting immediately after surgery for four months. The intervention group received additionally eight sessions of myofascial therapy from two up to four months after surgery. The control group received eight sessions of a placebo intervention, including static hand placements at the upper body region. Main measurements: The primary outcome was prevalence rate of upper limb pain. Additionally, pain intensity (Visual Analogue Scale (VAS, 0–100)), pressure hypersensitivity (pressure pain thresholds (PPTs; kg/cm 2 )) and pain quality (McGill Pain Questionnaire) were evaluated. All measurements were performed at 2 (=baseline), 4, 9 and 12 months post-surgery. Results: At 4, 9 and 12 months post-surgery, prevalence rates of pain, pain intensity and pain quality were comparable between the intervention and control group. PPT of the upper trapezius muscle was significantly higher in the intervention group at four months with a difference of −1.2 (−1.9 to −0.4) kg/cm 2, P = 0.012). PPT of the supraspinatus muscle was significantly higher in the intervention group at four months (−0.7 (−1.4 to −0.1) kg/cm 2, P = 0.021) and at nine months (−0.5 (−1.1 to 0.0), P = 0.040). Conclusion: Myofascial therapy has no added beneficial effect as standard physical therapy modality in the postoperative stage.